Bio‐marker detection redundancy improves sensitivity - Clanchy, FIL (Wiley, 2022)
Liquid biopsy for biomarker detection has the potential to revolutionise the management of cancer by reducing the time that tumours grow and metastasize undetected and untreated. As a relatively less invasive test, the frequency of testing is constrained more by the cost and ease of analysis, which are connected to the specificity and sensitivity of the method of detection. A recent study by Zhao et al. in Clinical and Translational Medicine indicates that multiple forms of detection from the liquid biopsy sample may improve sensitivity and demonstrates that seemingly incremental advances in clinical practice can significantly impact patient outcomes.